#TITLE_ALTERNATIVE# - RAHMAWATI PUTRI (NIM 10103047), HETI
A secret sharing scheme is a method of sharing a secret among participants in a system such way that each of participants must cooperate to reveal the secret. The secret, which is the main point, is known by them as a piece of information be directly unconnected with the secret. In this paper, it will be explained and compared four secret sharing schemes. The first one is Shamir's secret sharing schemes. The second one is secret sharing schemes based on Latin squares. The third one is secret sharing schemes based on edge-magic total graphs, and the fourth one is by Brickell's vector space. The last, secret sharing schemes based on Brickell's vector space is implemented within a program.